Human Dignity Curriculum: Teachers’ comfort, commitment, and perceived support teaching a new socioemotional learning curriculum - Law, Moira A. (Frontiers in Education, 2024)
Globally, young people are experiencing unprecedented levels of socio-emotional loneliness, stress, and uncertainty. Formulating insight into their own and others' experiences and behaviours is especially important during unsettling times and can be facilitated with socioemotional learning (SEL) curriculums. When implementing SEL programs, their success heavily depends upon teachers' levels of commitment and comfort with the curriculum, as well as their perceived support from the administration; this is important and rarely studied. The current phenomenological qualitative study examined teachers' experience during the early implementation of a new SEL, the Human Dignity Curriculum, (HDC) with middle school students in two small schools in Canada and the United States of America. Semi-structured interviews, using a four-question protocol developed for this study, were conducted with teachers who had completed teaching a ten-week module, as well as both school administrators. Written informed consent was obtained from each volunteer interviewee.Participants were asked, 1) Tell me about your experience while teaching HDC; 2) What was your commitment level to teaching HDC? 3) What was your comfort level with teaching HDC? 4) Did you feel supported by your administration when preparing and teaching HDC? Inductive thematic analysis identified five themes indicating HDC was a 1) user-friendly, 2) high value curriculum; 3) teachers felt supported teaching it; and a 4) shared language, 5) and shared teacher-student experience evolved when teaching HDC. Future research to replicate this initial evaluation of teachers' experience and exploration of HDC's potential impacts on youths' well-being and related behavioural outcomes appears warranted.